Dependent, but not Perfectionistic, Dysfunctional Attitudes Predict Worsened Mood and Appraisals after Emotional Support from a Romantic Partner - Felix, Steven A. M.; Hooker, Christine I. (Frontiers in Psychology, 2016)
Background: Receiving emotional support from a romantic partner often leads to emotional costs via negative appraisals about the self and one’s relationship, but it is unclear whether certain individuals are more susceptible to these costs. We evaluate whether the presence of perfectionistic and dependent dysfunctional attitudes leads to more negative effects of receiving emotional support from a romantic partner. Methods: Twenty-nine couples (27 men, 31 women; mean age 24.5) completed the Dysfunctional Attitudes Scale and then a daily online questionnaire by recording their mood, appraisals, and received emotional support. Mixed-effects regressions were used to evaluate whether perfectionistic and dependent dysfunctional attitudes moderated the relationship between emotional support receipt and subsequent mood and appraisals. Results: Perfectionism did not interact with emotional support but exerted a main effect of increasing negative moods and appraisals. Dependency interacted with emotional support such that those with more dependent attitudes, reported greater negative next-day moods and appraisals as a function of emotional support. Conclusions: Individuals with dependent, but not perfectionistic, dysfunctional attitudes are more likely to experience emotional and cognitive costs after receiving emotional support. These costs may stem from activation or exacerbation of the attitudes specific to dependency, including need for acceptance, support, and approval of others.